Rembrandt, master of the portrait - Bonafoux, Pascal (H. N. Abrams, 1992)
Traces the life and career of one of the world's greatest painters and analyzes Rembrandt's paintings, discussing the artist's use of light and assessing his powerful and perceptive portraits.